Surface vibration analysis (SVA): a new non-invasive monitor of gastrointestinal activity. Issue 1 (January 1989) - Campbell, F C; Storey, B E; Cullen, P T; Cuschieri, A
Abstract : A computerised system for measurement of vibration at the abdominal surface was constructed which was addressed to the evaluation of gastrointestinal (GI) motor function. Preliminary studies revealed a dominant low frequency signal which was synchronous with the heartbeat and was considered representative of aortic pulsation. This was excluded by selective spectral filtration. The remaining signal was processed and measured by computer, with provision of quantitative energy values as well as of graphic display. The developed method, called surface vibration analysis (SVA) has been evaluated clinically; (a) against oral to caecal transit times (OCCT) of a standard solid meal, in five patients with severe postgastrectomy diarrhoea, seven patients with mild idiopathic diarrhoea and 22 healthy volunteers. (b) against prokinetic effects of a gastrointestinal stimulant (cisapride) in nine patients. In (a) postprandial SVA energy measurements were greater (SVA [*X (SEM)] = 406, 933 (98, 224] and oral to caecal transit of the solid meal was more rapid (OCTT = *90 (29) min) in the severe diarrhoea patients [postgastrectomy] than either the mild diarrhoea group (*SVA = 235, 317 (50, 780); *OCTT = *199 (42) min) or normal volunteers (*SVA = 212, 062 (27, 153); *OCTT = 242 (19) min) [p less than 0.01 for SVA and OCTT]. In the total group, an inverse correlation was observed between quantitative SVA energy values and oral to caecal transit times of solids (Spearman's rho = -0.486; p less than 0.01). In (b), drug stimulation of the GI tract caused an increase of fasting SVA measurements from *21, 217 (5956) [before] to *41, 937 (9606) [after] intravenous cisapride (p less than 0.05). This new technique may be useful for evaluation of gastrointestinal motor activity.